Detection of SARS-CoV-2 in the air in Indian hospitals and houses of COVID-19 patients. (August 2022) - Moharir, Shivranjani C.; Thota, Sharath Chandra; Goel, Arushi; Thakur, Bhuwaneshwar; Tandel, Dixit; Reddy, S. Mahesh; Vodapalli, Amareshwar; Singh Bhalla, Gurpreet; Kumar, Dinesh; Singh Naruka, Digvijay; Kumar, Ashwani; Tuli, Amit; et al.
Abstract: To understand the transmission characteristics of severe acute respiratory syndrome corona virus-2 (SARS-CoV-2) through air, samples from different locations occupied by coronavirus disease (COVID-19) patients were analyzed. Three sampling strategies were used to understand the presence of virus in the air in different environmental conditions. In the first strategy, which involved hospital settings, air samples were collected from several areas of hospitals like COVID-intensive-care units (ICUs), nurse-stations, COVID-wards, corridors, non-COVID-wards, personal protective equipment (PPE) doffing areas, COVID rooms, out-patient (OP) corridors, mortuary, COVID casualty areas, non-COVID ICUs and doctors' rooms. Out of the 80 air samples collected from 6 hospitals from two Indian cities- Hyderabad and Mohali, 30 samples showed the presence of SARS-CoV-2 nucleic acids. In the second sampling strategy, that involved indoor settings, one or more COVID-19 patients were asked to spend a short duration of time in a closed room. Out of 17 samples, 5 samples, including 4 samples collected after the departure of three symptomatic patients from the room, showed the presence of SARS-CoV-2 nucleic acids. In the third strategy, involving indoor settings, air samples were collected from rooms of houses of home-quarantined COVID-19 patients and it was observed that SARS-CoV-2 RNA could be detected in the air in the rooms occupied by COVID-19 patients but not in the other rooms of the houses. Taken together, we observed that the air around COVID-19 patients frequently showed the presence of SARS-CoV-2 RNA in both hospital and indoor residential settings and the positivity rate was higher when 2 or more COVID-19 patients occupied the room. In hospitals, SARS-CoV-2 RNA could be detected in ICUs as well as in non-ICUs, suggesting that the viral shedding happened irrespective of the severity of the infection. This study provides evidence for the viability of SARS-CoV-2 and its long-range transport through the air. Thus, airborne transmission could be a major mode of transmission for SARS-CoV-2 and appropriate precautions need to be followed to prevent the spread of infection through the air. Graphical abstract: Image 1 Highlights: SARS-CoV-2 is detected in the air in COVID care areas in hospitals. Segregating COVID-care and non-COVID-care areas in hospitals can be effective in controlling air mediated spread. SARS-CoV-2 load is higher in air if a greater number of COVID-19 patients are present. SARS-CoV-2 captured from air can be infective.